2020
DOI: 10.1038/s41419-020-2278-6
|View full text |Cite
|
Sign up to set email alerts
|

A20 targets PFKL and glycolysis to inhibit the progression of hepatocellular carcinoma

Abstract: Abnormal expression of the E3 ubiquitin ligase A20 has been found in some malignant cancers, including hepatocellular carcinoma (HCC). Here, we discovered that A20 is an E3 ubiquitin ligase for phosphofructokinase, liver type (PFKL) in HCC A20 interacts with PFKL and promotes its degradation, therefore inhibiting glycolysis in HCC cell lines. Downregulation of A20 in HCC cells promotes proliferation, migration, and glycolysis, all of which can be inhibited by targeting PFKL with RNA interference. Importantly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 39 publications
5
51
1
Order By: Relevance
“…Apart from this, we proved that A20 played a crucial role in glycolysis, with the expressions of a series of glycolytic enzymes significantly decreased after the knockdown of A20. This finding was in contrary to two previous reports demonstrating that A20 exerted negative impact on glycolysis in hepatocellular carcinoma and leukemia 44,46 . The discrepancy may be due to the heterogeneity of distinct tumor types, which indicated that tumor context should be taken into consideration for A20-based metabolism intervention in cancer therapy.…”
Section: Discussioncontrasting
confidence: 99%
“…Apart from this, we proved that A20 played a crucial role in glycolysis, with the expressions of a series of glycolytic enzymes significantly decreased after the knockdown of A20. This finding was in contrary to two previous reports demonstrating that A20 exerted negative impact on glycolysis in hepatocellular carcinoma and leukemia 44,46 . The discrepancy may be due to the heterogeneity of distinct tumor types, which indicated that tumor context should be taken into consideration for A20-based metabolism intervention in cancer therapy.…”
Section: Discussioncontrasting
confidence: 99%
“…Phosphofructokinase (PFK), the second rate-limiting enzyme in glycolysis, is a key regulator of glycolytic flux in cancer cells. Decreased A20 mediated ubiquitination and degradation of PFK liver type (PFKL) are related to increased glycolysis during hepatocellular carcinoma progression [254]. Phosphorylation of PFK1 platelet isoform (PFKP) by AKT can prevent it from TRIM21mediated ubiquitination and degradation, promoting aerobic glycolysis in glioblastoma cells [255].…”
Section: Ubiquitination and Metabolic Enzymesmentioning
confidence: 99%
“…The A20-KO in hepatocytes results in chronic liver inflammation, as well as increased inflammation induction by pro-inflammatory stimulants like LPS or TNF, as well as enhanced susceptibility to HCC [ 125 ]. The protective properties of A20 towards HCC progression have been shown in another study, where A20 acts as an E3 Ub-ligase for a liver-type phosphofructokinase (PFKL) [ 133 ]. This leads to the inhibition of glycolysis and ceases cancerous proliferation, hence the evidence for the potential antitumor role of A20 emerges [ 133 ].…”
Section: Nf-κb-regulating Molecular Factorsmentioning
confidence: 99%